Analisis Pengaruh Pengelolaan Keuangan Daerah Dan Partisipasi Angkatan Kerja Terhadap Pertumbuhan Ekonomi Provinsi Jawa Timur - Dzaki Alfarrez, Muhammad; Mukhlis, Imam (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This study aims to examine the impact of local revenue, general and specific fund allocations, and labor force involvement intensity on economic growth in East Java Province. The focus is on East Java Province, covering 38 cities and regencies. This research uses secondary data, including the local revenue of 38 cities or regencies in East Java from 2018 to 2022, general and specific fund allocations, labor force participation, and economic growth. The study applies panel data regression analysis to determine the effect of variable x on variable y. According to the study's findings, local revenue has a positive but insignificant effect on economic growth. Specific fund allocations and labor force participation have a significant negative effect on economic growth in East Java Province. Meanwhile, general fund allocations have a positive effect on economic growth. The findings of this study are expected to be useful in evaluating and formulating policies aimed at sustainably increasing regional income in East Java cities or regencies through the empowerment of the local economy and the development of potential sectors.